Itna sara pani - Rehana, Asif; Hamza, Alvi Sakina, Kazmi (book group Karachi, 2002)
Itna Sara Pani is an Urdu children's book that explores the importance of water conservation. The book likely follows a narrative that highlights the value of water, its scarcity in certain regions, and the need to use it wisely. It might include stories about water cycles, water pollution, and the impact of human activities on water bodies.